Aerobic Biodegradation of Four Groups of Steroid Hormones in Activated Sludge - Jiaxin Zhang; Jun Luo; Hong Chang (Journal of Chemistry)
Steroid hormones in the environment have obtained considerable attention, as they can be harmful to aquatic organisms at very low concentrations. An analytical method was developed for simultaneously monitoring four estrogens, seven androgens, seven progestogens, and eleven glucocorticoids in a single water sample using liquid chromatography-electrospray tandem mass spectrometry. Laboratory studies were then performed to investigate the aerobic biodegradation of 29 steroids belonging to the four groups. The degradation of target steroids followed first-order reaction kinetics, and the degradation half-life (t1/2) of estrogens, androgens, progestogens and glucocorticoids was 1.2–8.7 h, 0.3–1.3 h, 1.4–7.7 h, and 1.4–23.1 h, respectively. Most of the esterified glucocorticoids were more persistent than the parent compounds, but the t1/2 for halogenated glucocorticoids was longer than that of their esterified compounds. In addition, C-21 ester glucocorticoids were more prone to decomposition than C-17 esters. Hydrolysis did not significantly affect the decomposition of esterified steroids.